Biowarfare, bioterrorism and biocrime: A historical overview on microbial harmful applications. (September 2020) - Oliveira, Manuela; Mason-Buck, Gabriella; Ballard, David; Branicki, Wojciech; Amorim, António
Highlights: Microorganisms have been use as weapons since pre-historic times. Biowarfare is the intentional use of biological agents as weapons in war scenarios. Bioterrorism is the intentional use of biological agents against a civilian population. Biocrime is the intentional use of biological agents against a specific individual. Microbial forensics can be applied to solve cases of BW, BT, and BC. Abstract: Microbial Forensics is a field that continues to grow in interest and application among the forensic community. This review, divided into two sections, covers several topics associated with this new field. The first section presents a historic overview concerning the use of microorganisms (or its product, i.e. toxins) as harmful biological agents in the context of biological warfare (biowarfare), bioterrorism, and biocrime. Each case is illustrated with the examination of case reports that span from prehistory to the present day. The second part of the manuscript is devoted to the role of MF and highlights the necessity to prepare for the pressing threat of the harmful use of biological agents as weapons. Preventative actions, developments within the field to ensure a timely and effective response and are discussed herein.